KEGIATAN EMPLOYEE RELATIONS DALAM UPAYA MENINGKATKAN PRODUKTIFITAS KERJA KARYAWAN MARIANI INTERNATIONAL HOTEL PADANG - Suryani, Yulie (EDUTECH CONSULTANT, 2017)
Mariani International Hotel Padang is a 3 star hotel (***) located at Jalan Bundo Kanduang 35 Padang. Mariani International Hotel Padang always seeks to members or workers who engage in such activities can provide achievements in the form of high productivity to achieve its intended purpose. Mariani international hotel in Padang employee relations activities have been very well built. It can be seen from the many programs that have been conceived and developed by internal party hotel. As the event gathering of employees and festivities, excursions, sport commonly called an informal discussion, with a variety of information regarding the state of the hotel, outbound training, training and others are all aimed to strengthen the relationship of all employees both fellow employees or between superiors and subordinates. So with the employee relations activities had created a strong team building, loyalty to the job and the company as well as the emergence of a sense of spirit in employees, which in turn can increase work productivity. Based on the results of this study concluded that in fact the age and taste of seniority is not an obstacle to productivity. Things that support increased productivity is the sense of family keakrapan and have a sense of empathy with Mariani International Hotel Padang.